Short Sales Contraints, Information Content of Stock Prices, and Seo Pricing - Charoenwong, C. (Institutional Knowledge at Singapore Management University, 2006)
This article examines the influence of SEC’s Rule 105, Regulation M, on informed trading and the information content of stock price surrounding the offer day of a seasoned equity offering (SEO). The results of this study show that the constraints on short sales imposed by the Rule inhibit informed trading and hamper the incorporation of information into the stock price for offers with private adverse information and without listings on the options market. These constraints contribute to a substantial increase in price uncertainty and market’s relatively more sensitive response to seller-initiated trading. After controlling for other potential causes of SEO discounts, such as price pressure and rent expropriation, our results show that the decrease in information content of stock price just before an offer day has a significant impact on the value discount of an SEO. The Rule’s restrictions on informed trading appear to cause overpricing of those stocks for which traders have access to private adverse information, which increases the pressure to sell on the offer day.